Órteses em PVC para membro superior: utilização por terapeutas ocupacionais brasileiros, propriedades físicomecânicas e de toxicidade e desempenhos funcional e mioelétrico - Silva, Larissa Galvão da (Universidade Federal de São Carlos, 2013)
Splints are devices whose function to stabilize, immobilize, prevent and correct deformities and maximizing the function and are currently manufactured in thermoplastic , especially low temperature. Was created a technique for making splints from thermoplastic PVC and high temperature due to the lack of scientific studies of the applicability of PVC for orthosis for the upper limb, proposed a study aiming to meet , compare and analyze aspects concerning the applicability of the materials and wrist splints made of two types of thermoplastics , the high temperature PVC and a low temperature Ezeform ®, commonly used for orthosis . The research involved the analysis of the factors for the use of materials, the analysis of the mechanical properties, thermal and toxicity of both materials and analysis of myoelectric and functional performances of subjects with and without orthoses on functional tests of manual dexterity . It was found that occupational therapists using PVC do this by being accessible in terms of cost of material and using Ezeform, the ease in modeling, PVC has high recyclability, and Ezeform, is more susceptible to deformation; functional performance volunteers with orthotics PVC and Ezeform is hindered significantly; especially with the PVC; the myoelectric activity of the upper fibers of the trapezius increases with both orthoses; especially with Ezeform of the biceps muscle did not change significantly and muscles radial extensor and flexor digitorum superficialis had the myoelectric amplitude decreased when the orthoses used and so that the orthosis with PVC myoelectric activity was lower.
Keywords: Aparelhos ortopédicos; Órteses; Materiais - testes; Capacidade motora; Eletromiografia; PVC; Destreza motora; Orthotic devices; Materials testing; Motor skills; Electromyography; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL